2011
DOI: 10.1002/jbm.b.31776
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronic acid nanofiber wound dressing—production, characterization, and in vivo behavior

Abstract: Hyaluronic acid (HA) was electrospun. The effects of flow rate, spin length, and the applied voltage on the diameter of the HA nanofibers were analyzed. The average thickness of the webs was 0.041 cm. The air permeability of sterilized HA nanofiber wound dressing was much higher than that of gauze with Vaseline. The degree of crystallinity of HA nanofibers was characterized using powder X-ray technique and was found to be 20.6%. A preclinical study was conducted to compare healing of wounds covered by an adhes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
80
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(87 citation statements)
references
References 23 publications
(22 reference statements)
3
80
0
4
Order By: Relevance
“…CF wound dressings, as well as NF wound dressings, showed a positive influence on wound healing, as determined by histological analysis. Hyaluronic acid nanofibers have been shown to be effective in promoting wound healing of full-thickness excisional wounds in pigs, and chitosan-poly(vinyl alcohol) nanofibers only showed a positive influence on wound healing when used in combination with R-Spondin I, a novel growth factor (52,53). Curcumin-loaded poly(ε-caprolactone) (PCL) also showed improved wound healing from day 6 compared to plain PCL over a 10-day period in a diabetic murine model (54).…”
Section: Discussionmentioning
confidence: 99%
“…CF wound dressings, as well as NF wound dressings, showed a positive influence on wound healing, as determined by histological analysis. Hyaluronic acid nanofibers have been shown to be effective in promoting wound healing of full-thickness excisional wounds in pigs, and chitosan-poly(vinyl alcohol) nanofibers only showed a positive influence on wound healing when used in combination with R-Spondin I, a novel growth factor (52,53). Curcumin-loaded poly(ε-caprolactone) (PCL) also showed improved wound healing from day 6 compared to plain PCL over a 10-day period in a diabetic murine model (54).…”
Section: Discussionmentioning
confidence: 99%
“…The HA is proved to be beneficial in wound healing applications since it plays major role in facilitating keratinocyte migration and proliferation, activating and moderating the inflammatory response, and reducing scar formation. A preclinical study was conducted to compare healing of wounds covered by an adhesive bandage, a sterilized solid HA, a gauze with Vaseline, an antibiotic dressing, and a sterilized HA nanofiber wound dressing on crossbred pigs as an experimental model [32]. The study results showed that the sterilized HA nanofiber wound dressing exhibited better healing efficiency than adhesive bandage, sterilized solid HA, and gauze with Vaseline dressing, but it was not statistically better than the antibiotic dressing.…”
Section: Natural Polymer Nanofibers As Wound Healing Scaffoldsmentioning
confidence: 99%
“…A variety of polymer-based nanofibers have been applied as wound dressings, including polyvinylalcohol [143], chitosan [130], gelatine [144], hyaluronic acid [145], collagen and collagen-based composites [146,147], polyethersulfone [148], and polyurethane/polyurethane nanocomposites [149,150]. Polyethersulfone (PES), a synthetic and biocompatible polymer, was electrospun into nanofibers and applied as an epidermal wound dressing, which proved to be effective in improving the skin healing [148].…”
Section: Polymer-based Nanofibers For Wound Dressingmentioning
confidence: 99%